Penggunaan Metode Blanded Learning Untuk Meningkatkan Pengetahuan Literasi Digital Mahasiswa Ilmu Komunikasi Fisip Universitas Mulawarman - Kheyene Molekandella Boer; Rina Juwita; Nurliah (IQTIDA : Journal of Da'wah and Communication, 2023)
Digital literacy in Indonesia is an issue that continues to be promoted, considering that the government continues to encourage the improvement of communication and information technology infrastructure. Indonesia still has digital literacy competencies that fall into the "adequate" category which means "not good", therefore this paper tries to see the extent of understanding of students from the social and political science faculty of Mulawarman University about digital literacy through mass communication courses. This research uses the method of filling out pre-test and post-test questionnaires using blended learning, namely collaboration in providing teaching materials using offline and online methods using learning videos. The result is an increase in understanding related to the 4 pillars of digital literacy belonging to the Ministry of Communication and Information; digital skills, digital culture, digital ethics, and digital security. Most students have sufficient understanding of digital literacy.